Modern Islamic Thinking and Activism Dynamics in the West and in the Middle East - Toguslu, Erkan (Leuven University Press, 2014)
Innovative research of 'Islam at work' in geographical and social contexts. 'Modern Islamic Thinking and Activism' presents a series of scholarly papers in relation to Islamic thinking, activism, and politics in both the West and the Middle East. The reader will apprehend that Islam is not the monolithic religion so often depicted in the media or (earlier) in the academic world. The Islamic world is more than a uniform civilization with a set of petrified religious prescriptions and an outdated view on political and social organization. The contributions show the dynamics of 'Islam at work' in different geographical and social contexts. By treating the working of Islamic thinking and of Islamic activism on a practical level, 'Modern Islamic Thinking and Activism' includes innovative research and fills a significant gap in existing work.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Social Science / Sociology; Social sciences; Electronic books